2022
DOI: 10.21203/rs.3.rs-1272893/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Occurrence and levels of persistent organic pollutants (POPs) in wild and farmed tilapia (Oreochromis niloticus) from Lake Kariba, Zambia: possible impact on fish health

Abstract: The current study was carried out to determine occurrence and levels of persistent organic pollutants (POPs) in wild and farmed tilapia (Oreochromis niloticus) in Lake Kariba, Zambia, and possible implications for fish health. Concentrations of organochlorine pesticides (OCPs), polychlorinated biphenyls (PCBs), polybrominated diphenyls (PBDEs), hexabromocyclododecane (HBCDD) and perfluoroalkyl substances (PFASs) were determined in liver samples of tilapia. Concentrations of POPs in wild tilapia were in gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Fish represent an essential ecological component of aquatic ecosystems and can accumulate to many different lipophilic contaminants [ 2 , 3 , 4 ]. Although several monitoring studies have shown that halogenated compounds, such as PCBs and PBDEs, have been decreasing in marine ecosystems over the past 10 years [ 5 ], these contaminants are still detected in fish from various FAO areas [ 6 , 7 ]. Exposure to these pollutants can occur through the skin and through respiration, but mainly, about 90% occurs through the diet, in which food of animal origin, particularly fish, plays a major role [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fish represent an essential ecological component of aquatic ecosystems and can accumulate to many different lipophilic contaminants [ 2 , 3 , 4 ]. Although several monitoring studies have shown that halogenated compounds, such as PCBs and PBDEs, have been decreasing in marine ecosystems over the past 10 years [ 5 ], these contaminants are still detected in fish from various FAO areas [ 6 , 7 ]. Exposure to these pollutants can occur through the skin and through respiration, but mainly, about 90% occurs through the diet, in which food of animal origin, particularly fish, plays a major role [ 8 ].…”
Section: Introductionmentioning
confidence: 99%